Sierra Leone : 2013 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Sierra Leone has made significant progress in macroeconomic stabilization over the last five years. Real GDP growth averaged some 7 percent, driven by output expansion in agriculture, mining, and services; as well as the scaling-up of infrastructure investment. Nonetheless, important impediments to broad-based growth remain, including large infrastructure gaps, insufficient energy supply, and limited access to safe water and sanitation. Medium-term prospects are positive. Growth is projected to remain robust, mainly driven by iron ore production and continued high public investment; while inflation is expected to decline further as monetary and fiscal policies remain prudent.